Porous and nanofiber α-chitosan obtained from blue crab (Callinectes sapidus) tested for antimicrobial and antioxidant activities. (January 2016) - Kaya, Murat; Dudakli, Fatma; Asan-Ozusaglam, Meltem; Cakmak, Yavuz Selim; Baran, Talat; Mentes, Ayfer; Erdogan, Sevil
Abstract: Chitin was isolated using the classical chemical method from the shell of Callinectes sapidus . The chitin content in the dry weight of the crab shells was determined as 12.1%. Total chitosan yield was recorded as 76%. The deacetylation degree of the chitosan was found to be 82.5%. The obtained chitin was in the α-form which was confirmed from the results of FTIR, TGA and XRD analyses. Resulting chitin showed DTG max value as 390 °C while in same regard chitosan show this value as 306 °C. Detailed information about the composition of pores and nanofibers was obtained using SEM. Disc diffusion method used for testing the antimicrobial activity, inhibition zone diameters of the chitosan from C. sapidus varied between 15.28 and 20.21 mm for human bacterial pathogens, between 15.51 and 16.25 mm for fungal pathogens and between 14.22 and 15.75 mm for fish bacterial pathogens, respectively. MBC and MFC values of the chitosan from C. sapidus were between 0.16 and 2.50 mg/mL. The results of DPPH and ferric ion reducing power activity used for determining the antioxidant activity of the chitosan, were found as IC50 : 5.99 and EC50 : 6.16, respectively. Highlights: Chitin content of the crab Callinectes sapidus . Physicochemical characterization of blue crab chitin and chitosan. Antimicrobial and antioxidant activity of blue crab chitosan.